Situational leadership style adopted by nurses in the hospital field - Karen Cristina Kades Andrigue; Leticia de Lima Trindade; Simone Coelho Amestoy; Carmem Lúcia Colomé Beck (Universidade Federal de Goias, 2016)
This study aimed to analyze Situational Leadership styles adopted by hospital nurses and their association with their personal and professional profile. This is a quantitative and descriptive study and the Hersey and Blanchard leadership model was used with nurses who work in hospitals. Data were collected through sociodemographic questionnaire and the Leadership Effectiveness and Adaptability Description. The more directive leadership style focused on persuasion was the most present. The activity sector showed a significant relation to the leadership style (p=00.1), demonstrating approximation between assistance and leadership profile. Although the population is composed of young group with a short time of performance, the predominance of the Coaching leadership style may limit the creativity and potential of team members for the focus to be focused on the task. Strategies to achieve high levels of maturity, can assist nurses in adopting more flexible leadership practices.